PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT DI KANTOR KELURAHAN MARAWI KECAMATAN TIROANG KABUPATEN PINRANG - HAIZAH HAIZAH; Muhammad Rusdi; Haeruddin Syarifuddin (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
The purpose of this study was to determine the effect of Public Service Quality on Community Satisfaction in the Marawi Family Office, Tiroang District, Pinrang Regency. The population in conducting this study were people with male and female gender, amounting to 1,342 family cards from three environments, the sampling technique used was the Slovin formula with the results of 93 people, taken based on cluster techniques. The type of research used is descriptive quantitative research, data collection techniques used are observation techniques, questionnaires, interviews and documentation. Data analysis techniques are data selection, data clarification, data tabulation, data standardization using the SPSS 21 application. Based on the research taken from the results of the questionnaire data processing, the recapitulation of the Public Service Quality variable with a percentage of 64 % is included in the